Strategi Kontemporer Partai-partai Politik di Indonesia 2004-2009 - Tryatmoko, Mardyanto Wahyu (Jurnal Penelitian Politik, 2004)
The public perception and choice to a specific political party or politician, which based on intuition or rationality, are absolutely depended on historical experiences and the rise o f discourse oj political parties and politicians’ behavior it selves. However, every performance o f political parties with all of their conflicting interests that happens to them is directly influenced by the electoral and parties system. On the other hand, this system converts votes in the polling booth into seats in the assembly and simultaneously converts the behavior o f political parties -including the politicians- on the intra or extra parliament. In the meantime, when the people are in deep participation towards democratization o f the electoral and parties system, will political parties be able to be more mature and wise as their role, including fairly competition during elections? Will the national bad experiences be made a sfu e l o f struggle that is stated in their programs? It is not false, if undecided voters and violence by the people because o f an endless oligarchy usually respond these questions. One of Solutions that can avoid it is the maturity o f political culture and the reinforcement o f parties system.